2013
DOI: 10.2217/fvl.13.5
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus Infection-Induced DNA Damage Response

Abstract: Parvoviruses are a group of small DNA viruses with ssDNA genomes flanked by two inverted terminal structures. Due to a limited genetic resource they require host cellular factors and sometimes a helper virus for efficient viral replication. Recent studies have shown that parvoviruses interact with the DNA damage machinery, which has a significant impact on the life cycle of the virus as well as the fate of infected cells. In addition, due to special DNA structures of the viral genomes, parvoviruses are useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 132 publications
2
36
0
Order By: Relevance
“…They bind the viral origin of replication, nick viral DNA (56), and play an important role in inducing apoptosis and cell cycle arrest (57). However, HBoV1 NS1 is the only parvovirus NS1 protein that has been reported to activate ATM, ATR, and DNA-PKcs and to induce hallmarks of DDR (58,59). The conventional cellular response to DNA damage involves signaling events initiated by damage to the cellular genome (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They bind the viral origin of replication, nick viral DNA (56), and play an important role in inducing apoptosis and cell cycle arrest (57). However, HBoV1 NS1 is the only parvovirus NS1 protein that has been reported to activate ATM, ATR, and DNA-PKcs and to induce hallmarks of DDR (58,59). The conventional cellular response to DNA damage involves signaling events initiated by damage to the cellular genome (60).…”
Section: Discussionmentioning
confidence: 99%
“…Although HBoV1 replication in HEK293 cells induced DDR signaling, this did not trigger arrest of the cell cycle, with a high percentage of transfected cells being in S phase. In other autonomous parvoviruses, the effects of the DDR on DNA replication in dividing cells are largely due to arrest of the cell cycle (59). Infection of Walter Reed/3873D (WRD) canine cells with MVC and ex vivo-expanded human primary erythroid progenitor cells with parvovirus B19 has been shown to induce a prolonged S phase, due to the infection-induced DDR (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The oxidant/antioxidant imbalance has been reported in pathogenesis of enteric viral diseases like feline coronavirus, bovine herpesvirus‐1, porcine reproductive and respiratory syndrome and rotavirus (De et al., ; Durgut, Ataseven, & Öztürk, ; Kayar et al., ; Stukelj, Toplak, & Nemec Svete, ). Recently, it has been observed that parvovirus infection is linked with oxidative stress, and marked enhancement of reactive oxygen/nitrogen species, lipid peroxidation, DNA damage and poor antioxidant reserve (Luo & Qiu, ; Nykky, Vuento, & Gilbert, ; Panda, Patra, Nandi, & Swarup, ). In recent years, emphasis has been given on the antioxidants as the potential drugs of interest for management of viral diseases (Beck, ; Chandrasena et al., ; Crump, Langston, Rajkarnikar, & Grayson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phosphorylation of Nups can occur in response to DNA damage, commonly detected in parvovirus infections (26,27), and can indicate an infection-induced functional change of Nup153 (28,29). Our analyses do not exclude the possibility of Nup153 becoming detached from the NPCs in infection.…”
mentioning
confidence: 70%